61.8k views
4 votes
Any helpers ? Pls it would be nice

Any helpers ? Pls it would be nice-example-1
User Pschwamb
by
4.6k points

1 Answer

2 votes

Answer:

x = -(-20)² ± √(-20)² - 4(16)(-6) / 2(16)

Explanation:

Given quadratic equation:

16x² - 20x - 6 = 0

Quadratic formula is given by:

x = -b² ± √b² - 4(a)(c) / 2a

16x² - 20x - 6 = 0

From the equation,

a = 16

b = -20

c = -6

x = -b² ± √b² - 4(a)(c) / 2a

x = -(-20)² ± √(-20)² - 4(16)(-6) / 2(16)

x = -(400) ± √(400) - (-384) / 32

x = -400 ± √400 + 384 / 32

x = -400 ± √784 / 32

x = -400 ± 28 / 32

x = (-400 + 28) / 32 or x = (-400 - 28) / 32

User Rion Williams
by
5.1k points